2011
DOI: 10.1002/smll.201101087
|View full text |Cite
|
Sign up to set email alerts
|

The Burning Rate of Energetic Films of Nanostructured Porous Silicon

Abstract: Between Early View online publication and issue publication, the authors became aware of an additional relevant reference. [23] Becker et al. reported fl ame propagation velocities for pSi impregnated with NaClO 4 on the order of 3000 m/s. In their work, the pSi was prepared by galvanic etching, and the velocity measurements were performed in a desiccator box under nitrogen at a relative humidity below 2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…Critical to the ultimate reactivity of the energetic films is the resulting size [34] and morphology [35][36][37] of the constituents that make up the film, often which are significantly affected by the intermixing and deposition processes. Such environments vary broadly as well, ranging from a gentle mixing, stirring, or coalescence processes [38], to more intense milling [39], swaging, [40] or sonication processes [12,41].…”
Section: Introductionmentioning
confidence: 99%
“…Critical to the ultimate reactivity of the energetic films is the resulting size [34] and morphology [35][36][37] of the constituents that make up the film, often which are significantly affected by the intermixing and deposition processes. Such environments vary broadly as well, ranging from a gentle mixing, stirring, or coalescence processes [38], to more intense milling [39], swaging, [40] or sonication processes [12,41].…”
Section: Introductionmentioning
confidence: 99%
“…Several of its material characteristics, including high surface area, energy density, and MEMS compatibility make PS a particularly interesting candidate for the field of energetic materials. Many forms of silicon have been used in energetic applications including silicon particles [8], nanowires and nanotubes [8], and on-chip etched porous silicon [1][2][3][4][9][10][11][12]. The most reactive of these is on-chip PS, which for over twenty years has been known to demonstrate explosive-like reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…The reactive wave propagation speeds reported previously range from the order of 1 m/s (Parimi et al, 2012(Parimi et al, , 2014a to several hundreds of m/s Parimi et al, 2012Parimi et al, , 2014aPlummer et al, 2011) to several thousands of m/s Churaman et al, 2010;Piekiel et al, 2014). Reactive wave propagation speeds of 3660 m/s reported by Piekiel et al (2014) are among the highest speeds reported for nEMs.…”
Section: Introductionmentioning
confidence: 64%
“…This process is believed to be the mechanism responsible for the permeation of the gases ahead of the luminous reaction zone. Plummer et al (2011) attributed the erratic and infrequent "flame jump" observed in Figures 3c and 3d to the detachment of the PS film from the silicon substrate due to the pressure build up within the porous layer. Such skipping has been observed at speeds ranging from < 10 m/s in our work to speeds above 3000 m/s in Piekiel et al's (2014) work.…”
Section: Effect Of Microscale Structures On Reactive Wave Propagationmentioning
confidence: 90%